Mengukur Efektivitas Penerapan Quick Count Berbasis Web pada Pilkada Intan Jaya - Ester Ayuk Pusvita; Deni Stevan Ranggup (Jurnal Teknologi dan Informatika, 2025)
This Internship (PKL) was conducted at the Office of the Election Supervisory Board (Bawaslu) of Intan Jaya Regency, focusing on the effectiveness of implementing a web-based Quick Count in the Intan Jaya regional elections. This report discusses the challenges and solutions in achieving accurate Quick Count results in Intan Jaya. The research was carried out using observation, interviews, and literature studies, and the obtained data were analyzed descriptively and qualitatively. The results indicate several challenges in implementing Quick Count in Intan Jaya, namely limited telecommunication infrastructure, lack of skilled human resources, difficulties in data verification, and security disturbances. Based on these findings, several solutions were proposed to address these challenges, including building adequate telecommunication infrastructure, enhancing human resource capacity through training and technical guidance, strengthening the data verification system, and improving coordination with security forces. These findings are expected to help improve the effectiveness of Quick Count in the Intan Jaya regional elections.